HAS HEMATOPOIETIC STEM CELL TRANSPLANTATION A ROLE IN THE TREATMENT OF CHILDREN AND ADOLESCENTS WITH ACUTE PROMYELOCYTIC LEUKEMIA? - Anna Maria Testi (Mediterranean Journal of Hematology and Infectious Diseases)
The past three decades have brought major therapeutic advances in the treatment of acute promyelocytic leukemia (APL) both in adults and children. The current state-of-the-art treatment with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) in combination or not with chemotherapy results in long-lasting remission and cure in more than 90% of newly diagnosed patients. These treatments have made relapse a rare event. The detection of PML-RARA transcript by polymerase chain reaction (PCR) during treatment and follow-up can predict a hematological relapse. All studies have suggested a survival benefit in patients with molecular relapse given pre-emptive therapy compared with those treated at the time of overt hematological relapse. ATO-based regimens, seem to be effective for the achievement of a second molecular complete remission (CR). Patients in second molecular CR, are generally considered candidates for autologous hematopoietic stem cell transplant (HSCT), while for those with persistent molecular disease, allogeneic HSCT could be offered if a suitable donor is identified.